PERSEPSI SISWA TENTANG KOMPETENSI MENJAHIT DI JURUSAN DESAIN KRIA TEKSTIL (DKT) SMK NEGERI 4 PARIAMAN - martin, leni; Syafri, Haswita; Idrus, Yenni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
This research is aimed to describe student’s perception about sewing competence in textile skill design depertement at SMK N 4 Pariaman with indicators: 1) pattern knowledge. 2) measurement technique 3) pattern making technique 4) cutting technique and 5) sewing technique. The descriptive research method is being used in this research. Then, percentage is used in data analysis. Related to it, the result of student perception about sewing competence shows that: 1) the peception about pattern knowledge is not good (63,6%), 2) the peception about measurement technique is good enough (65,2%), 3) the perception about pattern making technique is good enough (66,1%), 4) the perception about cutting technique is good enough (68,5%), 5) the perception about sewing technique is good enough (70,6%). In conclusion, the student peception about sewing competence in Textile Skill Design Department at SMK N 4 Pariaman is good enough. Key Word: Student perception, Sewing competence